Studi Kualitatif Program Persalinan di Fasilitas Kesehatan Masyarakat di Puskesmas Mata Kota Kendari - Hartati Bahar (Lembaga Pengembangan Kinerja Dosen, 2026)
The delivery program in health facilities is an effort to improve maternal and infant safety through integrated services. This study aims to analyze the implementation of the Delivery Program in the working area of Mata Community Health Center, Kendari City. The study used a qualitative approach with a case study design. Informants were selected purposively, consisting of midwives, integrated health post (Posyandu) cadres, and postpartum mothers. Data were collected through in-depth interviews and analyzed thematically based on input, process, and output components. The results showed that the program's success was supported by the availability of health workers, facilities and infrastructure, BPJS support, the role of cadres, and family support. The implementation process included antenatal care, ongoing education, pregnancy monitoring, interpersonal communication, and a referral system. The program had a positive impact in the form of increased maternal safety, reduced risk of complications, and increased public trust in delivery in health facilities. However, obstacles such as access to transportation, distance, and public knowledge remain challenges. This program effectively increases safe deliveries and contributes to reducing the risk of maternal and infant mortality.